Micro, Small and Medium Enterprises (MSMEs): Women’s Empowerment for Women Entrepreneurs - Fasya Adisa Raspati; Anissa Lestari Kadiyono (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the foundation for advancing the nation’s economy. According to the mapping of MSMEs actors in Indonesia, 64.5% of total MSMEs were micro-scaled enterprises managed by women. Expanding women’s businesses positively impacts economic recovery; therefore, women’s empowerment must be appropriately implemented. This study aimed to obtain empirical data regarding women’s empowerment in the fashion sector of MSMEs in Bandung. This research used a quantitative non-experimental approach with convenience sampling and was conducted with 115 women entrepreneurs of MSMEs in the online and offline fashion sector in Bandung. The research results show that women entrepreneurs of MSMEs with good women’s empowerment can help themselves improve their performance in entrepreneurship to create progress for women’s MSMEs. Education is a very important factor for women to be more empowered. An annual omzet on a Microscale allows women to be empowered and direct themselves better because they feel more competent with the risks of small-scale businesses. Women entrepreneurs must retain and expand their women’s empowerment to realise their inner potential to enhance the performance and business they are now conducting.